2016
DOI: 10.1021/acs.nanolett.5b04071
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Self-Heating and Heat Dissipation in Ultrascaled Nanowire Transistors

Abstract: Through advanced electro-thermal simulations we demonstrate that self-heating effects play a significant role in ultrascaled nanowire field-effect transistors, that some crystal orientations are less favorable than others (⟨111⟩ for n-type applications, ⟨100⟩ for p-type ones), and that Ge might outperform Si at this scale. We further establish a relationship between the dissipated power and the electrical mobility and another one between the current reduction induced by self-heating and the phonon thermal cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 30 publications
0
29
0
1
Order By: Relevance
“…It was demonstrated that the self‐heating effect is more dominant in the case of thinner individual nanostructures . The presence of a substrate under the nanostructure is also important because it leads to heat dissipation and decreases the local operating temperature …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the self‐heating effect is more dominant in the case of thinner individual nanostructures . The presence of a substrate under the nanostructure is also important because it leads to heat dissipation and decreases the local operating temperature …”
Section: Resultsmentioning
confidence: 99%
“…[43,44] The presence of a substrate under the nanostructure is also important because it leads to heat dissipation and decreases the local operating temperature. [45][46][47] Figure 4a shows the room temperature gas response of a ZnO: Al NW (20 μM) and a ZnO:Al NW (40 μM) to different concentrations of ethanol vapors (down to 50 ppm) in order to find out what concentration leads to a higher gas response. It can be observed that as in the case of UV response, the ZnO:Al NW (20 μM) possess a higher gas response to ethanol vapors Figure 4b shows the gas response to 1000 and 50 ppm of ethanol, 2-propanol, n-butanol, and ammonia vapors for ZnO:Al NW (20 μM), showing that a ZnO:Al NW can detect VOCs vapors even at much lower concentrations of VOCs (50 ppm).…”
Section: Resultsmentioning
confidence: 99%
“…The amount of dissipated power in a given component can be put in relation with the phonon-limited mobility µ ph of its underlying channel material 47 : the higher µ ph the less phonons are emitted and the less electrical power is converted into heat. To verify whether this statement is valid or not here, the phonon-limited electron mobility of single-layer MoS 2 , WS 2 , and AC black phosphorus, as computed with the "dR/dL" method 48 , is presented in Fig.…”
Section: Device Resultsmentioning
confidence: 99%
“…In order to validate the LOA + Padé approach, we use the 3D atomistic NEGF code OMEN [29,44,[51][52][53] in which a sp 3 d 5 s * TB model for electrons and a modified valence-force-field (VFF) method for phonons are implemented. OMEN is among the most sophisticated atomistic simulators of quantum transport of nano-devices.…”
Section: Applications To Electron and Phonon Transports In A Nanowirementioning
confidence: 99%